Investigation of combustion of a coal-methane-air suspension in a long closed channel - Moiseeva, Ksenia M.; Pinaev, A. V.; Vasilev, A. A.; Krainov, Alexey Yu; Pinaev, P. A. (Combustion, explosion, and shock waves)
Experimental data on the velocity of propagation of a combustion wave in a coal-methane-air mixture with respect to the walls of a closed channel for various concentrations of coal dust are presented. A physico-mathematical model of combustion of this mixture on the basis of equations of gas dynamics and mechanics of disperse media in the one-velocity one-temperature approximation is developed. In the proposed model, the velocity of propagation of the combustion wave with respect to the gas suspension and the burning rate of the coal dust particle are parameters of the model and are determined by providing the consistency between the computed and experimental results. A comparison of the calculated flame velocity with respect to the channel walls in a wide range of mass fractions of coal dust reveals reasonable agreement with the experiments. The proposed approach can be used for estimating the influence of coal dust combustion on the intensity of shock waves formed in coal mines in the case of accidental explosions of methane.